Thicker than water : a memoir - Washington, Kerry, 1977- (Little, Brown Spark, 2023)
In this profoundly moving and beautifully written memoir, the award-winning actor and activist provides an intimate view into both her public and private worlds as she chronicles her life's journey thus far, sharing how she discovered her truest self and, with it, a deeper sense of belonging.